2017
DOI: 10.1177/0363546517712505
|View full text |Cite
|
Sign up to set email alerts
|

Successful Return to Sport After Arthroscopic Shoulder Stabilization Versus Nonoperative Management in Contact Athletes With Anterior Shoulder Instability: A Prospective Multicenter Study

Abstract: Collegiate contact and collision athletes with in-season anterior shoulder instability are significantly more likely to successfully return to sport without subsequent instability events the next season if they undergo surgical repair in the off-season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
87
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 32 publications
1
87
1
2
Order By: Relevance
“…Findings are relevant to athletes engaged in overhead sporting activities 1,3 where deficiencies in thoracic extension may place more stress on other components of the kinetic chain resulting in pain, altered performance, and impact on an athlete's ability to train and compete. 1 Whilst a recent review found inconclusive evidence of a relationship between static thoracic posture and shoulder complaints, 15 functional kinetic chains are dynamic, requiring a variable mix of movement, motor control, and strength across the component parts, including the thoracic spine to enable performance of skilled functional Upper thoracic Crosbie et al 38 Extension 2 [1,3] Lateral flexion (Ipsilateral) 3 [2,3] Rotation (Ipsilateral) 7 [5,9] Lower thoracic Crosbie et al 38 Extension 6 [4,8] Lateral flexion (Contralateral) 3 [2,4] Rotation Rotation (Ipsilateral) 7 [5,9] Lower thoracic Crosbie et al 38 Extension 2 [1,2] Lateral flexion (Contralateral) 7 [5,8] 38 Stewart et al 37 Extension…”
Section: Unilateral Shoulder Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings are relevant to athletes engaged in overhead sporting activities 1,3 where deficiencies in thoracic extension may place more stress on other components of the kinetic chain resulting in pain, altered performance, and impact on an athlete's ability to train and compete. 1 Whilst a recent review found inconclusive evidence of a relationship between static thoracic posture and shoulder complaints, 15 functional kinetic chains are dynamic, requiring a variable mix of movement, motor control, and strength across the component parts, including the thoracic spine to enable performance of skilled functional Upper thoracic Crosbie et al 38 Extension 2 [1,3] Lateral flexion (Ipsilateral) 3 [2,3] Rotation (Ipsilateral) 7 [5,9] Lower thoracic Crosbie et al 38 Extension 6 [4,8] Lateral flexion (Contralateral) 3 [2,4] Rotation Rotation (Ipsilateral) 7 [5,9] Lower thoracic Crosbie et al 38 Extension 2 [1,2] Lateral flexion (Contralateral) 7 [5,8] 38 Stewart et al 37 Extension…”
Section: Unilateral Shoulder Movementmentioning
confidence: 99%
“…Complaints are not however limited to arm‐dominant sports with comparable levels of 47% seen in football and 54% in swimming . Many studies have investigated approaches to management of sport‐related shoulder injuries, for example of the rotator cuff, acromioclavicular, and glenohumeral joints; with many athletes likely managed conservatively in line with current clinical guidelines . Notwithstanding implementation of evidence‐based management, many athletes go on to experience recurrent problems, with one report suggesting a 72% re‐injury rate for young athletes with shoulder instability …”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of anterior shoulder instability (ASI) has been well-studied in both cohorts treated nonoperatively 5 , 10 , 16 and operatively. 1 7 , 14 , 20 , 24 Neer et al 15 were among the first authors to describe glenohumeral arthritis as a consequence of recurrent shoulder instability, and numerous studies since then have identified a high rate of glenohumeral arthropathy.…”
mentioning
confidence: 99%
“…The prognosis of anterior shoulder instability (ASI) has been well-studied in both cohorts treated nonoperatively 5 , 10 , 16 and operatively. 1 7 , 14 , 20 , 24 Neer et al 15 were among the first authors to describe glenohumeral arthritis as a consequence of recurrent shoulder instability, and numerous studies since then have identified a high rate of glenohumeral arthropathy. 2 , 3 , 6 , 7 , 16 Hovelius and Saeboe 10 reported that 55% of patients who sustained a first-time anterior shoulder dislocation before the age of 40 years displayed some degree of arthropathy on radiographs after 25-year follow-up.…”
mentioning
confidence: 99%
“…reports American Academy of Orthopaedic Surgeons, American Orthopaedic Society for Sports Medicine, and American Shoulder and Elbow Surgeons (board or committee member); Arthrex (IP royalties; paid consultant; paid presenter or speaker); Arthroscopy (editorial or governing board); Arthroscopy Association of North America (board or committee member); International Society of Arthroscopy, Knee Surgery, and Orthopaedic Sports Medicine (board or committee member); Joint Restoration Foundation ( have greater, or even partially increased risk of recurrence, the time to stabilize is early after dislocation. [4][5][6][7][8] What is increasingly demonstrated in the literature is that there is a cost to recurrence of instability of the glenohumeral joint. There is no question that with more recurrent instability events (meaning heredmore than 2), there are (1) more anterior labroligamentous periosteal sleeve avulsion (ALPSA) tears, which carry with them an increased risk of failure after surgical stabilization 9,10 ;…”
mentioning
confidence: 99%